Antimicrobial Effects of Chrysophyllum albidum on Bacterial Isolates from Urinary Catheters (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Aqueous and ethanolic extracts obtained from Chrysophyllum albidum plant parts (leaves, roots, and seeds) were used to evaluate the potential antibacterial activity against bacteria isolated from urinary catheter tips. The following isolates were recovered: P. aeruginosa (7), S. aureus (15), E. coli (11), P. mirabilis (11), and K. aerogenes (6). The agar well diffusion method was used. The average percentages of antimicrobial resistance to gentamicin among the isolates were 45.5% for P. aeruginosa, 42.1% for E. coli, 46.9% for K. aerogenes, and ˃90% for the other isolates. The ethanolic extract mixtures (leaf, root, and seed) had the greatest effect on all the isolates, with inhibition zones (IZs) ranging from 8 to 26 mm and MICs ranging from
Keywords: Chrysophyllum albidum; Antibacterial; Extracts; Phytochemicals; CAUTI